Acceptability of Clitoria Ternatea and Zingiber Officinale Var Rubrum Rhizoma Formulations in the Form of Herbal Tea - Kushayati, Nuris; Siswantoro, Edy; Supriani, Anik (Universitas Islam Lamongan, 2024)
Body immunity is an important factor that must be considered. This is because the body's immunity will provide sufficient protection to the body so that it can avoid various threats of infection. One effort that can be made to increase the body's immunity so that it is in optimal condition is by consuming the herbal tea formulation of clitoria ternatea and zingiber officinale var rubrum rhizome. Therefore the purposse of this research is to analyze the acceptability of clitoria ternatea and zingiber officinale var rubrum rhizoma formulations in the form of herbal tea preparations. This organoleptic research uses an affective test which is based on measuring liking (acceptance). This affective test uses a hedonic scale. Observations for organoleptic tests are carried out using a hedonic scale. The ingredients used in this research were butterfly pea flower simplicia (clitoria ternatea L) and red ginger juice. The herbal tea formulations of butterfly pea flower and ginger are presented randomly with a certain code where each code represents a formulation of butterfly pea flower and ginger rhizome. The number of formulations tested was 5 formulations. From the results of the research that has been carried out, it was found that most of the panelists in this study tended to like the herbal tea formulation of clitoria ternatea and zingiber officinale var rubrum rhizoma with a composition of 20% clitoria ternatea and 80% zingiber officinale var rubrum rhizoma